Assessing the quality of existing clinical practice guidelines for chemotherapy drug extravasation by appraisal of guidelines for research and evaluation II - Masoud Bahrami; Tayebeh Karimi; Ghasem Yadegarfar; Ali Norouzi (Iranian Journal of Nursing and Midwifery Research, 2019)
Background: Extravasation is a potentially hazardous event that may occur during chemotherapy. The aim of this study is to assess the quality of existing Clinical Practice Guidelines (CPGs) for chemotherapy drug extravasation by Appraisal of Guidelines for Research and Evaluation II (AGREE II). Materials and Methods: Valid electronic databases and CPGs from 2007 to August 2018 were searched by keywords of CPGs, extravasation, chemotherapy, and cancer. CPGs were evaluated independently by five experts through AGREE II tool, and the consensus among evaluators was calculated by ICC (Intra-class Correlation Coefficient). Results: Five of the 111 CPGs matched the inclusion criteria. The methodological quality of CPGs in domains of “scope and purpose,“ “stakeholder involvement,“ “clarity of presentation,“ and “applicability“ were good, in the domain of “rigor of development,“ was acceptable, and in “editorial independence“ domain, it needed more attention of developers of CPGs. The range of assessors' consensus was within a range of moderate to very good (0.55--0.93). Conclusions: The methodological quality of existing CPGs of chemotherapy drugs extravasation assessed by AGREE II tool is appropriate. Four CPGs had high level while one had moderate level of quality. Therefore, their use is recommended in the clinic to reduce the risk of chemotherapy extravasation to the entire treatment team and the nurses working in the oncology departments.